2008
DOI: 10.1007/s00330-008-0882-4
|View full text |Cite
|
Sign up to set email alerts
|

Skull base: pseudolesion or true lesion?

Abstract: The skull base is a complex anatomical structure. Therefore, radiologists often use "side-to-side" comparison for detection of abnormalities. This approach is compromised by the high frequency of anatomical variations involving the skull base and the common presence of flow-related artifacts within vessels at the skull base that might mimic true lesions. The spectrum of "pseudolesions" ranging from different anatomical variations, such as unusual arachnoid granulations, asymmetric pneumatization and/or appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This might be true especially in case of brain stem masses due to artifacts, limiting imaging of the skull base and below [3,24,26].…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…This might be true especially in case of brain stem masses due to artifacts, limiting imaging of the skull base and below [3,24,26].…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…The radiological evaluation of this complex anatomical region requires a great deal of expertise and involves many potential pitfalls because the appearance of fissures, sutures and neurovascular channels closely resembles the appearance of fractures [6,7]. Depending on their location, fractures of the skull base can cause severe damage.…”
Section: Introductionmentioning
confidence: 97%
“…The emissary veins of the foramina rotundum and ovale form a venous plexus surrounding the enclosed nerves [16,19,41]. The FO venous plexus is the main pathway of the cavernous sinus drainage to the pterygoid venous plexus [19] and it is the main factor influencing the FO size [31]. Williams et al [41] in their study regarding the trigeminal nerve and the perineural vascular plexus found that the dimensions of the venous plexus surrounding the mandibular nerve were larger compared to the dimensions of the venous plexus compassing the maxillary nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the ESF location and content forced Wood-Jones [42] to view the ESF as an extension of [31] mentioned that the confluence ESF-FO and the transmission of the sphenoidal emissary veins via the FO, in the absence of the ipsilateral ESF is a possible explanation for the FO asymmetry. The hypothesis tested in this paper, is that the ESF may alter the FO venous part and thus the FO size.…”
Section: Discussionmentioning
confidence: 99%